G77(P) Socioeconomic and maternal reproductive factors affecting low birth weight babies in central nepal. (12th March 2018) - Shrestha, M; Gupta, SK; Sarmah, BK; Baidya, M
Abstract : Introduction: Low Birth weight is one of the most sensitive and reliable predictors of health and also an essential determinant of mortality, morbidity and disability in infancy and childhood. Globally, about one sixth of all newborns are low birth weight (LBW<2500 grams), which is the single most important underlying risk factors for neonatal deaths. It is estimated that 18 million babies are born with Low Birth Weight and half of them are born in south Asia. Over three –quarters of newborns death in Nepal occur in LBW babies. The estimates of prevalence of LBW in Nepal have ranged from 14% in community based studies to 32% in hospital based ones, overall being 27%. Objectives were to study the various socioeconomic and maternal reproductive factors related to low birth weight babies in Central regional part of Nepal. Material and Methods: Cross-sectional and observational study was undertaken from October 2012 to September 2014 comprising of 350 singleton live born baby admitted in NICU of Tertiary Care Teaching Hospital, Chitwan. Results: The common risks factors for LBW were significantly associated with low socio- economic status, maternal age, maternal education, occupation of mother, maternal smoking, maternal alcohol intake, number of ANC visit with significant p-value of <0.05. Conclusion: LBW mostly associated with maternal factors can be addressed directly by improving the socioeconomic factors (maternal age, educational level and economic status) and health status of pregnant women by supplementations, family planning services and female education.